Contribution of Physical Fitness Component to Health Status in Elderly Males and Females over 60 years - Short Report - Antonio Ignacio Cuesta-Vargas; Alejandro Galán-Mercant (AOSIS, 2012)
The purpose of this study was to identify the physicalfitness (PF) level of a cohort of elderly people that are subjected tophysical activity (PA), and to establish a regression model for theevaluation of health status (HS) of elderly people based on their PF.This is a Cross-sectional study. Consists of 114 Participants over60 years old, that were recruited from a physical activity program.Were measured variables about anthropometric characteristics,jumping tests with jumping platform, dynamic and static balance, riskof falls, lung capacity, HS and quality of life (QoL). We used Pearson'slinear correlation with 95% Zr. We looked for simple and multiple regression models. We used the bayesianinformation criterion approach and statistical inference to find and calculated a numerical estimate of thebest regression model. We used the dependent variable physical function of SF-12. Physical fitness variablesselected for the models were weight, height, Countermovement Jump test (flight time), Functional Reachtest, lumbosacral flexion mobility, Extended Timed Get Up and Go (ETGUG) (10 meters time score andtotal time score). The HS and QoL measurement are important for the prevention of injury during physicalexercise and should be conducted whenever is possible. The regression models proposed in this study can beused as an initial screening of HS or QoL at fitness facilities and fitness clubs that do not provide HS or QoLquestionnaires. However, these models are not an alternative to health care for a detailed determination ofHS and is not intended for use as a final evaluation.